Pengaruh dewan direksi wanita pada pelaporan tanggung jawab sosial perusahaan 2017 -2021 - Tang, Sukiantono; Sari, Ayu Widya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Corporate social responsibility is an effort made by the company in carrying out its responsibilities to stakeholders such as employees, the community, shareholders, consumers, and the surrounding environment. The percentage of women on the board of directors is also related to the results of corporate social responsibility and the strength of the analysis. This study aims to examine the effect of the female board of directors on corporate social responsibility reporting. This study uses quantitative methods and analysis with panel data regression. The population in this study were companies listed on the Indonesia Stock Exchange (IDX) from the period 2017 to 2021. The sample selection technique used purposive sampling and obtained 304 companies, so the total sample obtained for 5 years was 1463 research samples. The results of this study prove the influence of female board of directors on corporate social responsibility. Overall, it shows that the number of female directors has a positive effect on social responsibility, the percentage of female directors hurts corporate social responsibility, the female dummy has no effect on social responsibility, and the female audit committee ratio has no effect on social responsibility and the female expert director ratio does not. affects corporate social responsibility and has a Prob value (F-statistic) showing a value of 0.000000 from <0.05 and the value of Adjusted R-squared shows a value of 0.549845 or 54.98%.